The relationship between sarcopenia and cognitive dysfunction in bladder tumor patients - Kalyon, Semih; Özkan Gümüşkaya, Perihan; Özsoy, Neslihan; Özcan, Mustafa; Aydın Yoldemir, Şengül; Toprak, İlkim; Altun, Özgür; Akarsu, Murat; Özgün Çil, Eylem; Arman, Yücel; Tükek, Tufan (Journal of Surgery and Medicine, 2020)
Aim: There is no study in the literature to show whether there is a negative effect of sarcopenia on cognitive functions in patients over 65 years of age in the early postoperative period, who were operated under general anesthesia. The aim of this study was to determine the relationship between sarcopenia and cognitive dysfunction in the early postoperative period of transurethral resection of bladder tumor operation in the elderly population with bladder cancer. Methods: The cognitive functions of patients over the age of 65 years who underwent transurethral resection of bladder tumor were evaluated before and 24 hours after the surgery with mini-mental tests in this single center, cross sectional study. All patients underwent a preoperative gait test and muscle mass was measured. The muscle strength of the patients with walking speed >0.8 m / sec in the walking test was measured by hand grip dynamometer. Low walking speed and muscle mass, and normal walking speed, but with low handgrip power and muscle mass were the accepted criteria of Sarcopenia. Results: In the early postoperative period, a decrease in cognitive functions was observed in the population of 54 geriatric patients, 43 of whom were male. The mean age was 74 years in both sarcopenic and non-sarcopenic groups. Cognitive dysfunction was more common in the sarcopenic patient group of 15 patients in the early postoperative period compared to the non-sarcopenic group of 39 patients (P=0.001, P=0.026 respectively). However, this decrease in cognitive function in sarcopenic patients was not statistically significant compared to non-sarcopenic patients (P=0.644). Conclusion: We demonstrated that cognitive functions decreased in early postoperative period in the geriatric patient population. The decrease in postoperative cognitive functions in sarcopenic patients was higher than that in non-sarcopenic patients, although the difference was not statistically significant. Therefore, larger studies with more patients are needed to achieve a statistically significant difference.